Qualitative Study of Stakeholder Perceptions Related to Requirements for Elimination of Dog Rabies in Sri Lanka by 2025 - Ubeyratne Janrabelge, Kamalika Harshini; Srikitjakarn, Lertrak; Pfeiffer, Dirk Udo; Narapity Pathirannehalage, Sunil-Chandra; Kohnle, Lisa; Chaisowwong, Warangkhana; Hemwan, Phonpat (Open Science Journal, 2019)
Rabies has been eliminated in some Asian countries including Japan, Singapore, Maldives, and Hong Kong. Sri Lanka is close to joining that group: human rabies cases declined from 288 in 1975 to 23 in 2017, due largely to intradermal post-exposure prophylaxis. The weakest link in rabies elimination in Sri Lanka is inconsistent prevention at the source due in part to insufficient institutional capacity to achieve the goal of 70% dog vaccination coverage. Obstacles to rabies control identified through focus groups and in-depth interviews with stakeholders, government officials, non-government agents, and community residents include insufficient motivation for disease reporting and development of a clear protocol for disease reporting by the public, lack of awareness in some areas of the importance of disease reporting exacerbated by logistical issues, uneven vaccination coverage due to insufficient communication regarding government vaccination campaigns, and incomplete implementation of government policies. Other issues included a need for more responsible dog ownership and better understanding of rabies disease risks amongst dog owners. Dog-associated factors included the need for improved understanding of drivers of variation in dog population size, for lower sterilization cost to owners, and for monitoring of post-surgical complications. An integrated national dog rabies monitoring and reporting system based on effective partnerships among relevant institutions plus additional decentralized dog rabies diagnosis laboratories plus additional local veterinary and medical government staff are needed.